Cetaceans and sea turtles in the northern region of the Mediterranean Cetacean Migration Corridor: abundance and multi-model habitat suitability analysis - Cardona, Luis; Amigó, Natalia; Ouled-Cheikh, Jazel; Gazo, Manel; Chicote, Carla A. (Frontiers in Marine Science, 2025)
The Mediterranean Cetacean Migration Corridor is one of the largest marine protected areas in the Mediterranean Sea. Nevertheless, little is known about the abundance and distribution of cetaceans and sea turtles in the area. A combination of aerial and boat surveys conducted in 2023 revealed the presence of seven cetaceans and two sea turtle species therein. The community was dominated numerically by two epipelagic foraging species, the striped dolphin (Stenella coeruleoalba) and the loggerhead turtle (Caretta caretta). However, based on population estimates, the majority of the community biomass was contributed by sperm whales (Physeter macrocephalus) and fin whales (Balaenoptera physalus). The population numbers of Cuvier’s beaked whales (Ziphius cavirostris) and Risso’s dolphins (Grampus griseus) were in between. When migrating fin whales were excluded from the analysis, deep divers with a high trophic position (sperm whales, Cuvier’s beaked whales and Risso’s dolphins) made a much larger contribution to the overall community biomass than epipelagic predators with a lower trophic position (striped dolphins and loggerhead turtles). Bottlenose dolphins (Tursiops truncatus), long-fined pilot whales (Globicephala melas) and leatherback turtles (Dermochelys coriacea) were observed during the surveys, but were too scarce to attempt any population estimate. Random forest models and generalized additive models identified the concentration of chlorophyll-a and the eastward current velocity as the major drivers of the distribution of epipelagic species. Conversely, the distribution of deep divers was best explained by a combination of bathymetric (standard deviation of the slope) and hydrographic (eddy kinetic energy, sea surface height and eastward or northward sea water velocity) variables. Finally, the distribution of fin whales was poorly predicted by the environmental variables considered. This evidence indicates that dynamic spatial closures might be needed to reduce the impact of fishing and maritime traffic on epipelagic predators, whereas static closures might suffice for deep divers.